Late cretaceous Mosasaurs (Squamata: Mosasauroidea) from the maastrichtian of Marambio (=Seymour) Island, Antarctica - Reguero, Marcelo A. (2015)
Fil: Reguero, Marcelo A. Universidad Nacional de La Plata. Museo de La Plata. Instituto Antártico Argentino. Buenos Aires, Argentina.